2010
DOI: 10.1111/j.1748-7692.2010.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Kamchatkan fish‐eating killer whales to playbacks of conspecific calls

Abstract: Killer whales produce repertoires of stereotyped call types that are primarily transmitted vertically through social learning, leading to dialects between sympatric pods. The potential function of these call repertoires remains untested. In this study, we compared the reaction of Kamchatkan fish‐eating killer whales to the playbacks of calls from the same and different pods. After the playback of recordings from a different pod, in three cases whales changed the direction of their movement toward the boat, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…where TL is noise transmission loss, R is distance from the noise source (Filatova and Fedutin, 2011). The signal to noise ratio is an important issue whilst examining the masking potential of animal vocalisations.…”
Section: Resultsmentioning
confidence: 99%
“…where TL is noise transmission loss, R is distance from the noise source (Filatova and Fedutin, 2011). The signal to noise ratio is an important issue whilst examining the masking potential of animal vocalisations.…”
Section: Resultsmentioning
confidence: 99%
“…Where drift in call features occurs, it seems to happen at the level of matrilines or groups of related matrilines called pods (Miller et al, 2004;Deecke et al, 2010). Playback experiments with groups of killer whales off Kamchatka found that the whales matched calls of pod members but not calls from different pods (Filatova et al, 2011). It is possible the killer whales are also capable of matching calls at the level of regional clans (Weiß et al, 2011).…”
Section: Research Articlementioning
confidence: 99%
“…The evidence for bottlenose dolphin vocal learning is strong thanks to experimental tests on individuals under free-ranging, semicontrolled and controlled conditions. Similar experimental tests are needed in killer whales, but only one experimental study has exposed groups to short-term playback of calls under free-ranging conditions (Filatova et al, 2011). However, individuals can be exposed to different dialects in adventitious cross-fostering and cross-socializing experiments when killer whales from different vocal traditions are housed together in oceanaria (Bain, 1986).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that a subset of these whistles may serve as contact calls. Contact calls are known from bottlenose dolphins (Janik and Slater 1998), and elements of the killer whale dialect are used in the context of maintaining contact (Filatova et al 2011). In bottlenose dolphins, for which the evidence of contact function is strongest (Janik and Slater 1998), whistles promote group cohesion and reunions after separation (Janik and Slater 1998, Shapiro 2006, Sayigh et al 2007, Harley 2008, Quick et al 2012.…”
Section: With Bottlenose Dolphins)mentioning
confidence: 99%